x*2 + x*3 + x*4 + x*5 + x*6 = x*9 + 9999
=> x*(2 + 3 + 4 + 5 + 6) = x*9 + 9999
=> x*20 = x*9 + 9999
=> x*20 - x*9 = 9999
=> x*11 = 9999
=> x = 909
xx2 + xx3 +xx4+ xx5 + xx6 =xx9 + 9999
xx2 + xx3 + xx4 + xx5 + xx6 -xx9 = 9999
xx*10+2+ xx*10+3+xx*10+4+xx*10+5+xx*10+6-xx*10+9 = 9999
(xx*10+xx*10+xx*10+xx*10+xx*10-xx*10) + (2+3+4+5+6-9) = 9999
xx * (10+10+10+10+10-10) + 11 = 9999
xx*(10*5-10) = 9988
sai đề rồi
nhầm lầ sau viết đề bài cho rõ nhé
x * 2+x*3+x*4+ x*5+x*6 =x*9+9999
x * 2+x*3+x*4+ x*5+x*6-x *9 = 9999
x*(2+3+4+5+6-9) = 9999
x * 11 = 9999
x = 9999 : 11
x = 909
Vậy x= 909